2021
DOI: 10.3390/en14185836
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Assessment and Regulatory Aspects of Cold Ironing Planning for a Maritime Route in the Adriatic Sea

Abstract: The technology of cold ironing (or shore-to-ship power) can meaningfully reduce greenhouse gases and air pollutant emissions from ships at the berth by powering the vessels from the electrical shore grid. While cold ironing constitutes an effective and affordable solution in northern Europe and America, economic, legal, and environmental factors still render this technology less attractive in southern Europe. This paper aims to unpack and analyze the economic, regulatory, and environmental factors that can fos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 42 publications
(82 reference statements)
0
14
0
Order By: Relevance
“…In contrast, the fuzzy analysis indicated that long payback period is the most important barrier, although high investment cost remained one of the most important causal factors in the model. In other words, high investment cost is a critical barrier to including ports in the EU ETS according to both empirical studies (Davies, 2006;Dai et al, 2018Dai et al, , 2019Peng et al, 2019;Gianoli and Bravo, 2020;Piccoli et al, 2021) and the views of selected experts in managerial position in certified green ports in T€ urkiye. In short, ports have financial concerns regarding the potential benefits from participating in the EU ETS carbon trading market.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In contrast, the fuzzy analysis indicated that long payback period is the most important barrier, although high investment cost remained one of the most important causal factors in the model. In other words, high investment cost is a critical barrier to including ports in the EU ETS according to both empirical studies (Davies, 2006;Dai et al, 2018Dai et al, , 2019Peng et al, 2019;Gianoli and Bravo, 2020;Piccoli et al, 2021) and the views of selected experts in managerial position in certified green ports in T€ urkiye. In short, ports have financial concerns regarding the potential benefits from participating in the EU ETS carbon trading market.…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion of these two barriers related to leakage into the effect group supports the model's construction due to the structure of these barriers that is sensitive to incentives. Piccoli et al (2021) evaluated the payback period of the cold ironing system, which is thought that it will be useful with the EU ETS. Similarly, our model included the investment payback period as a barrier.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Martínez-López et al [32] evaluated the efect of emission reduction of shore power and LNG in Switzerland by calculation method. Piccoli et al [33] analyzed the regulatory, economic, and environmental elements that could facilitate SP as a standard installation in the Mediterranean Sea.…”
Section: Literature Reviewmentioning
confidence: 99%